Maintenance of oral hygiene in intensive care patients: The role of Hospital Dentistry (Research, Society and Development, 2022)
The present study aimed to verify the role of Hospital Dentistry through the importance of the Dental Surgeon in the maintenance of oral hygiene in patients of Intensive Care Units and, consequently, in the prevention of oral pathologies or potential aggravation of preexisting diseases. This is an integrative literature review. The search was carried out in the PubMed, SciELO and Lilacs databases, including articles published in Portuguese and in the 10-year period (2012-2022). According to the established criteria, 25 articles were selected, addressing the topic of maintaining oral hygiene in patients in intensive care. It was concluded that maintenance of oral hygiene is a key factor to prevent the action of infectious agents, which highlights the importance of the Dental Surgeon in Intensive Care Units for the restoration of quality of life through hospital dentistry, since patients hospitalized patients depend on professionals to carry out effective oral hygiene procedures, due to the lack of autonomy, which leads to poor hygiene. Associating this fact with the use of drugs and equipment and the depressed systemic condition, the accumulation of bacteria in the oral cavity promotes a facilitated proliferation for the whole organism, causing imbalance, which affects the entire immune system, harming the health of the hospitalized patient.